Father Absence and Masculinity Formation Among Young Men: A Public Practical Theological Exploration of Emotional Development and Relational Identity - Thalukanyo Cloepatra Mufunwa Sadiki; Lufuluvhi maria Mudimeli (F1000Research, 2026)
Background The lack of a father figure poses a significant challenge not only for society but also for how boys form their own identity through emotion and personal growth. While there has been a large amount of research published on how boys form masculinity based on behaviour and social constructs, there is limited empirical research that has examined men’s masculine identity from a public perspective of practical theology. Methods Nevertheless, this study’s qualitative desktop methodology will draw on available literature from theology and other disciplines related to fathering and masculinity, attachment theory, emotional development, and relational identity as the primary research source. The two major theoretical frameworks used in this paper are Connell’s hegemonic masculinity theory and attachment-based theories. Results This study finds that boys’ understanding of masculinity is influenced, in part, by their relationships with role models. Growing up without a father, boys often rely on their peers, media, and society for information about masculinity. This lack of support has caused boys to feel disconnected emotionally and relationally. Recommendation Based on these results, the authors of this study recommend that practical theology should be concerned with the absence of fathers and their impact on boys’ needs for support in developing healthy masculine identities and in emotional functioning. Conclusion The research findings make clear that fatherlessness is not only a social but also a theological issue, affecting the development of emotions and masculine identity among young men, and emphasizing the importance of faith communities in mentoring and identity formation.